2015
DOI: 10.1007/s11517-015-1320-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of glucose prediction models for patients with type 1 diabetes mellitus applying sensors for glucose and physical activity monitoring

Abstract: The present work presents the comparative assessment of four glucose prediction models for patients with type 1 diabetes mellitus (T1DM) using data from sensors monitoring blood glucose concentration. The four models are based on a feedforward neural network (FNN), a self-organizing map (SOM), a neuro-fuzzy network with wavelets as activation functions (WFNN), and a linear regression model (LRM), respectively. For the development and evaluation of the models, data from 10 patients with T1DM for a 6-day observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 28 publications
1
42
0
1
Order By: Relevance
“…There are a few works to date using DL for glucose forecasting. For instance, in [10], [16] traditional dense neural networks were used but without exploiting the advantages of deep layers. In [17], two latent layer neural networks were adopted for hypo/hyperglycemia prediction.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few works to date using DL for glucose forecasting. For instance, in [10], [16] traditional dense neural networks were used but without exploiting the advantages of deep layers. In [17], two latent layer neural networks were adopted for hypo/hyperglycemia prediction.…”
Section: Introductionmentioning
confidence: 99%
“…ANNs have been used in a great number of diagnostic decision support systems for medical applications, and they have demonstrated good predictive power (Buller, Buller, Innocent, & Pawlak, 1996;Verma & Zakos, 2001;Zarkogianni, Vazeou, Mougiakakou, Prountzou, & Nikita, 2011;Zarkogianni et al, 2015b). Ensembles of ANNs (EANN) can improve both the generalization abilities and the performance of an individual ANN, by compensating with each other the errors produced by each ANN (Sharkey, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that more sophisticated prediction algorithms, also exploiting other signals like the amount of insulin injected or physical activity, can be employed, e.g., those of Zhao et al [9,12], Zecchin et al [13,41], Turksoy et al [10], Zarkogianni et al [11], and Georga et al [42,43]. …”
Section: The Past: the “Smart” Cgm Sensormentioning
confidence: 99%
“…From a clinical point of view, it has been widely demonstrated that the additional information provided by CGM sensors, when used in conjunction with SMBG data, improves the quality of glucose control [7,8]. From an academic point of view, the availability of CGM data stimulated, over the last 15 years, the development of several CGM-based applications, e.g., algorithms for the prediction of future glucose concentration to generate preventive hypo/hyperglycemic alerts [9,10,11,12,13], for the real-time modulation of the basal insulin administration [14,15,16], and for the detection of faults with glucose sensor–insulin pumps system [17,18,19,20,21]. Even more interesting is that CGM sensors enabled the realization of the artificial pancreas (AP), i.e., a device designed mainly for Type 1 diabetes (T1D), which is aimed at maintaining the BG concentration within the safety range by automatically injecting insulin via an insulin pump controlled by a closed-loop control algorithm [22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%